Waste to energy incineration technology Recent development under climate change scenarios - Khan, Muhammad Sajid (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2022)
With the huge generation of municipal solid waste (MSW), proper management and disposal of MSW is a worldwide challenge for sustainable development of cities and high quality of citizens life. Although different disposal ways are available, incineration is a leading harmless approach to effectively recover energy among the applied technologies. The purpose of the present review paper is to detail the discussion of evolution of waste to energy incineration and specifically to highlight the currently used and advanced incineration technologies, including combined incineration with other energy, for instance, hydrogen production, coal and solar energy. In addition, the environmental performance is discussed, including the zero waste emission, leachate and fly ash treatment, climate change contribution and public behaviour. Finally, challenges, opportunities and business model are addressed. Trends and perspectives on policies and techno-economic aspects are also discussed in this review. Different simulation tools, which can be used for the thermodynamic assessment of incineration plants, are debated; life-cycle inventory emissions and most critical environmental impacts of such plants are evaluated by life-cycle analysis. This review shows that waste incineration with energy yield is advantageous to handle waste problems and it affects climate change positively